Students’ Vocabulary Mastery through Word Wall at SMPN 44 Surabaya - Siti Fatimah (JournEEL, 2020)
The aim of this research was to find out how far the Word Wall to improve students’ vocabulary mastery at SMPN 44 Surabaya. Classroom action research was applied to the 40 students of the class 7-D as the subjects of this research. In applying the Word Wall, there were two cycles applied consisting of three meetings for each cycle. The researcher used the students’ tests result to measure the improvement of their vocabulary achievement. The results of this research showed the increasing students’ vocabulary mastery proven by the results of the tests conducted. Mean of the pre-test was 50 and mean of the post-test in cycle I was increased becoming 70. Then, mean of post-test in cycle II was significantly improved in 93. The research was stopped in the cycle II in regard of the criteria of success was 82.5%. The researcher found out there were a significant students’ vocabulary mastery after implementing the Word Wall. it is recommended English teachers who teach vocabularies should apply the Word Wall Strategy regarding can help students easily to understand the content of the texts. For the students, they can use and have more exercises with the Word Wall to enrich their vocabularies in daily activities. For other researchers, it is suggested to conduct the similar research by exploring the areas of focus in other English skills.